Edukasi Cara Menjaga Kesehatan Reproduksi dan Pencegahan Penyakit Menular Seksual pada Siswa/siswi SMA N 7 Pekanbaru sebagai Latihan Public Speaking Mahasiswa Kebidanan Universitas Abdurrab - Suci Shinta Lestari; Neneng Oktavianti; Sri Rahmawati; Noor Afriyanni Yuwandari; Putri Dwi Retno; Aurelia Fridons (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Adolescent health is one of the most important parts of developing quality human resources during adolescence. Individuals experience profound physical, emotional and social changes during their teenage years, which can affect their well-being performance. An in-depth understanding of reproductive wellbeing is essential to help adolescents identify risks of sexually transmitted infections (STIs), unintended pregnancy and mental health problems. All cases of HIV infection worldwide occur in people under 25 years of age. 111 million cases of sexually transmitted infections are reported by those under 25 years of age. Adolescents are particularly vulnerable to STDs, including HIV and AIDS, due to their lack of knowledge about the disease and consequently about 67% of new HIV/AIDS cases in developing countries occur among young adolescents (aged 15-24 years). Meanwhile, nearly 60% of unwanted pregnancies occur among adolescents in developing countries, and 15 million adolescents have given birth. Many adolescents still do not have access to education that supports knowledge about these issues, due to lack of knowledge about these issues they are often trapped in myths and misinformation.